Mimarî ve estetik unsurlarıyla aynı dönemde farklı coğrafyalarda inşa edilmiş iki islâm sarayı; Elhamra ve Kubâdâbâd - OCAK AHMED, SÜMEYRA (My University, 2023)
Saray, mekânsal özellikleri ile hem hükümdar ve ailesinin yaşadığı hem de devlet yönetiminin yürütüldüğü yerdir. Hükümdarın özel yaşam alanı ve idare merkezini bünyesinde bulundurması itibariyle devletler saray mimarisine ayrı bir önem vermiştir. Estetik ve sanatsal özellikleri ile saraylar, temsil ettiği devletin kültür, medeniyet ve sanat özellikleri yanında siyasi ve ekonomik gücünü yansıtmaları bakımından da önemlidir. Araştırmamızın amacı, tarih boyunca iktidarın en büyük sembollerinden olan ve gücün mimarideki yansıması kabul edilen saray yapılarının coğrafyaya göre nasıl şekillendiğini ortaya koymaktır. Bu sebeple İslâm coğrafyasının farklı bölgelerinde aynı yüzyılda inşa edilmiş Kubâdâbâd Sarayı ve Elhamra Sarayı örnek iki yapı olarak seçilmiştir. Bu iki yapı plan, mimari ve tezyinî unsurlarıyla ayrı ayrı incelenmiş; karşılaştırma yapılarak İslâm coğrafyasının farklı bölgelerinde inşa edilmiş sarayların benzer ve farklı yönleri tespit edilmeye çalışılmıştır

The palace is both the place where the Sultan and his family lived and the state administration was carried out. Due to being the private living space and the monarch’s administrative center, the states placed special emphasis on the palaces’ architecture. With their aesthetic and artistic characteristics, palaces are important in terms of reflecting the political and economic power as well as the cultural, civilization, and art characteristics of the state they represent. This research aims to reveal how the palace structures, considered one of the major symbols of monarchs and the reflection of power in architecture throughout history, were shaped according to geography. For this reason, Kubâdâbâd Palace and Alhambra Palace, which were built in the same century in different parts of the Islamic geography, are chosen as two exemplary buildings. These two structures are examined in detail by considering their plan, architectural and ornamental elements. And thus the similar and different aspects of the palaces built in different parts of the Islamic geography are determined by making comparisons.
Alhambra and kubadabad: Two islamic palaces built in different geographies at the same period and their architectural and aesthetic elements
Keywords: Islamic Architecture; Decoration; Palace; Dar-al-Imara; Anatolian Seljuks; Nasrids; Konya; Andalusia; Kubadabad; Alhambra; İslâm Mimarisi; Tezyînat; Saray; Dârülimâre; Anadolu Selçukluları; Nasrîler; Endülüs; Kubâdâbâd; Elhamra